Analysis of traditional Chinese medicine syndrome types and frequency changes of CD8+ and CD25+ T cells in metabolic-related fatty liver disease: Metabolism-related fatty liver CD8+CD25+T cells - Zong, Xiangyu; Zhang, Haiyan; Yang, Tianyi (Cellular and Molecular Biology, 2023)
This study aimed to observe and analyze the changes in traditional Chinese medicine (TCM) syndrome types and CD8+ and CD25+T cell frequencies of metabolic-related fatty liver disease. For this purpose, 100 patients with metabolic-related fatty liver disease and their TCM syndrome types who were screened for medical treatment were collected. Flow cytometry was used to detect the changes in the frequency of CD8+ and CD25+T cells in the peripheral blood of patients, as well as liver function, fasting blood glucose, and lipid index. The frequency differences of CD8+ and CD25+T cells in patients with different syndrome types were compared. To use partial correlation analysis to determine the correlation between CD8+, CD25+T cell frequencies and TCM syndrome types in patients. Results showed that a total of 30 cases of liver stagnation and spleen deficiency syndrome, 25 cases of phlegm turbidity internal obstruction syndrome, 20 cases of dampness heat stasis syndrome, and 25 cases of phlegm stasis mutual accumulation syndrome were included in the 100 MAFLD patients. There was statistical significance (P<0.01) in the comparison of ALT, AST, GGT, TC, TG, HDL-C, LDL-C, FPG, HOMA-IR, CD8+CD25+, CD8+CD25-, CD8-CD25+, and CD8-CD25- among patients with different TCM syndrome types. There is a positive correlation between TCM syndrome types and patients' CD8+CD25+, CD8+CD25-, and CD8-CD25+, while there is a negative correlation between them (P<0.05). From the chord diagram, the relationship between CD8+CD25+ and TCM syndrome types is the closest. The ROC curve was used to analyze and determine that the relevant standard for CD8+CD25+ in liver depression and spleen deficiency syndrome is <4.90%; The relevant standard for phlegm turbidity internal obstruction syndrome is 4.90%~7.88%; Damp heat stasis syndrome is 7.88%~8.20%; The syndrome of phlegm and blood stasis accumulation is more than 8.20%. The TCM syndrome types of metabolic-related fatty liver disease will vary with the frequency of CD8+ and CD25+T cells. In conclusion, TCM syndrome types are closely related to the severity of the patient's condition and immune function, providing a new perspective and means for understanding the pathogenesis of metabolic-related fatty liver disease and evaluating the condition.